DYNAMICS OF PSYCHIATRIC SYMPTOMS IN CUSHING'S SYNDROME - Tatyana Telbizova; Ivan Aleksandrov; Mariana Arnaoudova (Peytchinski Publishing, 2020)
Cushing's syndrome may present with various psychiatric disorders which can lead to a misdiagnosis at the beginning, deterioration of the course of the disease and life-threatening complications. The most common psychiatric disorder is atypical depression. During the initial stages of the disease, the somatic symptoms of Cushing's syndrome can be subtle, difficult to identify, especially when the psychiatric symptoms are dominant. Objective: The aim of the present article is to report a case of a 24-year-old woman with a Cushing's syndrome, caused by the adrenal adenoma. The onset of the disease is a suicidal attempt. Family history is significant for psychiatry disorder. The belated diagnosis led to somatic and psychiatry complications of the disease - sepsis and persisting high suicidal risk. The dynamic change in the patient's mental state - from a severe depressive episode with atypical symptoms to psychosis with single catatonic symptoms - correlated well with the gradual increase of the plasma cortisol levels. The antidepressant and subsequent antipsychotic medication turned out to be ineffective. The surgical treatment, followed by a normalization of the cortisol levels was a key to the successful outcome and the reduction of self-aggression risk. Conclusion: The early diagnosis and timely treatment of Cushing's syndrome decrease the risk of multiple complications. The shift from atypical depression to psychosis with catatonic symptoms correlates with the worsening of the hormonal imbalance. The signs of atypical depression in Cushing's syndrome, resistant to the antidepressant medication, could be considered as relatively specific symptoms, guiding specialists to its somatogenic origin for the proper diagnosis.